Family Ownership in Indonesia, Good or Bad? - Annisa Aghniarahma Junia (The International Journal of Business Review (The Jobs Review), 2022)
Indonesia is one of the countries that adopt the two-tier system, where there are separation functions between directors and commissioners. Indonesia is also dominated by family firms. In relation to the agency problem, the concentration of ownership by the family in the company and the existence of independent directors in the company's board of directors are two things that are importantly considered as corporate governance practices. This study aims to find out how family ownership in Indonesia influences the demands of corporate governance practices and examines how independent directors moderate those relationships. The study used 69 companies listed in the ASEAN Corporate governance Scorecard with a four-year study period from 2012 to 2015. Using the regression method of panel data, this study found that the greater the family ownership of firms in Indonesia, the smaller the company's demands to good corporate governance practices. While the independence of directors and the size of the board moderate the relationship positively.Keywords: Corporate governance, Family firms, Independent director, Agency theory